THE DEVELOPMENT OF ANDROID-BASED “HIRUTER” INTERACTIVE MULTIMEDIA IN INDONESIAN LESSONS IN CLASS II SD - Ika Sri Wahyuni; Erma Suryani Sahabuddin; Nurhaedah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
The development of interactive multimedia